Invertebrates of the jarrah forest - Majer, Jonathan; Abbott, I. (1988)
In this chapter we review ecological and economic investigations which have been performed on jarrah forest invertebrates. This coverage reflects the range of work which has been undertaken and is arranged in the following sections. First, some basic information on the abundance, composition and role of soil and litter invertebrates is presented. This is followed by a section on the ways in which these forest animals are influenced by some natural disturbances and by others caused by humans. The next two sections outline the ecological investigations which have been performed on ants and earthworms and, in the last section, the insects damaging the trees themselves are described. The biology and pest status of the jarrah leaf miner (Perthida glyphopa), the most important insect pest of jarrah, is described in detail in Chapter 9.